COVID-19 Delta Variant-of-Concern: A Real Concern for Pregnant Women With Gestational Diabetes Mellitus - Mamun, Md Mahfuz Al; Khan, Muhammad Riaz (Frontiers in Endocrinology, 2021)
The emergence of the COVID-19 Delta variant-of-concern (VOC), a novel variant of SARS-CoV-2, has threatened the total health systems throughout the world. This highly contagious strain is spreading at a higher exponential rate than any other variants of COVID-19 by infecting and subsequently killing hundreds of thousands of people globally. Among the most sensitive groups, pregnant women are at high risk of increased hospitalization, pneumonia, respiratory support, and admission to intensive care units during the Delta period. Pregnant people with gestational diabetes mellitus (GDM) are at increased chances of Delta VOC infection. GDM patients are nine and three times more likely to be infected by Delta VOC than those pregnant patients suffering from diabetes and cardiovascular diseases and hypertension, respectively. Additionally, they are more vulnerable to Delta VOC infection than wild-type and Alpha COVID-19 VOC ones. Thus, this review critically sheds light on the current scenario of the vulnerability of pregnant mothers, especially those with GDM, to Delta VOC infection.